CLINICAL PROFILE AND OUTCOME OF PATIENTS PRESENTING WITH ACUTE UPPER GI BLEEDING IN A TERTIARY CARE CENTRE OF WESTERN NEPAL - Chaudhary, Shatdal; Shakya, Smriti; Jaiswal, Niraj Kumar; Shahi, Aakash; Dhakal, Pushpa Raj; Chaudhary, Nagendra (Journal of Universal College of Medical Sciences, 2018)
Introduction: Acute upper gastrointestinal (UGI) bleeding is a common medical emergency which is associated with significant morbidity and mortality. The annual incidence of UGI bleeding varies from 48 to 160 cases per 100,000 populations in the United States of America (USA), with a mortality rate of 7% to 10%. The aetiology and outcome of UGI bleeding varies significantly in different geographic regions depending on the demographic and socioeconomic characteristics of the local population. This study was done to evaluate the clinical profile and outcome of patients presenting with acute UGI bleeding at a tertiary care centre in Lumbini zone of Nepal. Material and Methods: This was a hospital based prospective observational study. All the patients who presented with acute UGI bleeding and fulfilled the inclusion criteria from 1st August 2013 to 31st July 2014 were included in the study. The study was cleared by the ethical review committee of the institute and written informed consent was taken from all the patients. Results: During the study period, 70 patients fulfilled the inclusion criteria and were subjected to statistical analysis. The mean age of patients in the present study was 55.11 ± 19.93 years. The majority of patients (30, 43%) were elder, belonging to the age group of more than 60 years. There were 55 (79%) male and 15 (21 %) female. The patients were mostly farmers by occupation accounting 29 (41 %) cases. Ethnically, 26 (3 7%) patients of UGI bleeding were from janajati group where majority of them had esophageal varices. Overall, the peptic ulcer disease was the leading cause of UGI bleeding seen in 26 (37%) patients followed by esophageal varices seen in 23 (33%) patients. 0 positive was the commonest blood group which was found in 28 (40%) of our patients. In our study 44 (63%) patients were alcohol consumers and 37 (53%) had coexisting comorbidities that added for the UGI bleeding related complications. During admission, 7 patients expired causing 10% mortality. Conclusion: Acute UGI bleeding was commonly seen in older age group patients with male preponderance. Peptic ulcer disease was the leading cause of the UGI bleeding. The mortality rate was found to be 10%. The mortality also increased with increasing age and patients with pre-existing co morbidities. Journal of Universal College of Medical Science Vol. 6, No. 1, 2018, Page: 3-7